A comparison of personality type congruence with learning achievement of students from the primary school teacher education program at Adzkia University - Irwan Prayitno; Ismira Ismira (Jurnal Konseling dan Pendidikan, 2023)
Personality type can be defined as an image of oneself manifested publicly. John Lewis Holland argues that personality type influences career choices and job satisfaction. Holland's Career Theory states that the most congruent personality types for a teacher's career are social, entrepreneurial, and artistic personality. The personality types that are less suited for a teaching role include the investigative, conventional, and realistic types. This research aimed to compare the congruence or incompatibility of personality types with the learning achievement of Primary School Teacher Education students at Adzkia University. This comparative quantitative study used the personality test arranged based on the concept of Hexagonal Theory by John Holland. The research sample comprised 161 selected using a simple random sampling technique. The research results show that 60% of the students' personality is congruent with their job as a teacher, whereas the remaining 40% shows the opposite. The average academic achievement of student’s personality congruent with their job as a teacher is 81.6, while student personality opposite is 78.9. There is only a 2.1 point difference between the two. Furthermore, there is no difference in the learning achievement of students with the congruent personality type and those without. The hypothesis test result shows that personality type has no impact on learning achievement.